2017
DOI: 10.1186/s13071-017-2035-6
|View full text |Cite
|
Sign up to set email alerts
|

An effective method for the identification and separation of Anopheles minimus, the primary malaria vector in Thailand, and its sister species Anopheles harrisoni, with a comparison of their mating behaviors

Abstract: BackgroundSpecies of the Anopheles minimus complex are considered to be the primary vectors of malaria in South and Southeast Asia. Two species of the complex, Anopheles minimus and Anopheles harrisoni, occur in Thailand. They are sympatric and difficult to accurately distinguish based on morphological characters. The aim of this study was to investigate the potential of antennal sensory organs to distinguish these two species. Additionally, we investigated their ability to mate in cages of different sizes, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…aconitus accounted for 57 percent of the total and represented more than 10 percent of the total number of the mosquitoes collected. It should be noted that recently, Taai et al, [24] indicated that this species is morphologically closely resemble An. minimus but is not part of the Minimus complex, and can be listed as part of the Funestus Group.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…aconitus accounted for 57 percent of the total and represented more than 10 percent of the total number of the mosquitoes collected. It should be noted that recently, Taai et al, [24] indicated that this species is morphologically closely resemble An. minimus but is not part of the Minimus complex, and can be listed as part of the Funestus Group.…”
Section: Discussionmentioning
confidence: 74%
“…minimus s.s. and An. harrisoni are members of the Minimus Complex [24]. The Minimus Complex includes three species, An.…”
Section: Sibling Species Identi Cationmentioning
confidence: 99%
“…takasagoensis (Takano et al ., 2010), An. minimus (Taai et al ., 2017), An. maculipennis (Novikov and Vaulin 2014), An.…”
Section: Major Cryptic Species In Mosquitoesmentioning
confidence: 99%
“…This complex system comprises preferences involving communication signals that lead to stimulation between potential mates and ultimately the choice of a mate. Comparative studies that emphasize divergence of behaviours in sister insect species, such as male courtship behaviour, female contact pheromones and courtship song, are increasing (Wijit et al ., ; Taai et al ., ). Such comparative behavioural analysis can improve existing SIT or help to develop new tactics of vector mosquito control by gauging mate competitiveness.…”
Section: Introductionmentioning
confidence: 97%